Technology-Based Teaching Material Development Training for Pre-Service Teachers to Improve Students’ Learning Outcomes - Fakhruddin, Zulfah; Selle, Amzah; Nurchalis, Nur Fadillah (NOBEL: Journal of Literature and Language Teaching, 2019)
This research aimed to examine the effectiveness of technology-based English teaching material development training to improve students’ learning outcomes. This research used quasi-experimental design. The instrument of this research was a multiple-choice test. In collecting data, the writers applied pre-test, treatment, and post-test to students. There were four pre-service teachers who involved in the treatment of this research. Two of them taught in experimental classes and the other two taught in control classes. Pre-service teachers who taught in experimental classes had been trained for ten meetings, while those who taught in control classes had not been trained. This research used SPSS 17 to analyze the data. The result of this research found that there was significant difference of students’ learning outcomes between experimental and control classes after having the treatment. Students’ learning outcomes in experimental classes was higher than in control classes. The effect size of significant level after calculated by Eta squared was 0,042. Event though it had small effect, the technology-based English teaching material training given to the pre-service teachers was quite effective to improve students’ learning outcome in MTs Negeri Parepare.